ANALISIS PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2010-2014) - Rahmawati, Nursakinah Bina; Handayani, Rr. Sri (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to analyze the effect arising from the characteristics of corporate governance by proxy size of the board of directors, the independence of the board of commisioners and the size of the audit committee; the ownership structure with a proxy family ownership, institutional ownership, public ownership and foreign ownership of the company’s performance. Dependent variabel in this research is the company’s performance measured by Tobin’s Q. This study uses secondary data collected from Indonesia Stock Exchange. The reserach data is the annual financial statement of the firms in the manufactur sector for the period 2010-2014. The sampling method in this study is purposive sampling. And at the last, this study used 220 firms-years observations. This study uses multiple reggresion analysis. Based on the result of hypothesis test,there are a positive effect among the size of the board of directors, audit committees and public ownership on company’s performance measured by Tobin's Q. On the other hand, there are  no  effect  among  the  independence  of  the  board  of  commissioners,  family  ownership, institutional ownership and foreign ownership on company’s performance.